Hubungan Dukungan Keluarga Terhadap Pemanfaatan Buku KIA Pada Ibu Hamil - Mar’atun Shalihah; Nur Azizah Indriastuti (Universitas Malahayati Lampung, 2025)
ABSTRACTMaternal and child health books play an important role in education and early detection of health problems among pregnant women and children. However, its utilization is still low due to lack of family support. MCH book utilization is highly dependent on family support, especially the active role of husbands. This support can be realized through assistance during pregnancy checks, helping to understand the contents of the MCH book, and applying health information in everyday life. Emotional support from husbands also plays a major role in maintaining the psychological well-being of pregnant women. Husband involvement from the beginning of pregnancy can increase the mother's motivation to maintain her health, and encourage timely seeking of medical assistance. Therefore, husband's readiness and knowledge are crucial factors in creating a healthy and safe pregnancy. This study aims to determine the relationship of family support to the utilization of the MCH book. This study used a non-experimental quantitative approach with a cross sectional design. The sample consisted of 74 pregnant women who performed ANC at the Kasihan 1 Bantul Health Center, Yogyakarta, selected through random sampling technique. Data were collected using family support questionnaires and MCH book utilization. The results showed that the majority of respondents were 20-35 years old (90.5%), had a high school education (52.7%), did not work (70.3%), and were multigravida (70.3%), and as many as 38 (51.4%) respondents were in the third trimester of pregnancy, and (50.0%), respondents had a low level of family support but still utilized the MCH book, namely 41 (55.4%). The chi-square test showed a significant relationship between family support and MCH book utilization.Keywords: Family Support, MCH BookABSTRAKBuku kesehatan Ibu dan Anak (KIA) berperan penting dalam edukasi dan deteksi dini masalah kesehatan ibu hamil dan anak. Namun, pemanfaatannya masih rendah akibat kurangnya dukungan keluarga. Pemanfaatan buku KIA sangat bergantung pada dukungan keluarga, khususnya peran aktif suami. Dukungan tersebut dapat diwujudkan melalui pendampingan selama pemeriksaan kehamilan, membantu memahami isi buku KIA, serta menerapkan informasi kesehatan dalam kehidupan sehari-hari. Dukungan emosional dari suami juga berperan besar dalam menjaga kesejahteraan psikologis ibu hamil. Keterlibatan suami sejak awal kehamilan mampu meningkatkan motivasi ibu untuk menjaga kesehatannya, serta mendorong pencarian bantuan medis secara tepat waktu. Oleh karena itu, kesiapan dan pengetahuan suami menjadi faktor krusial dalam menciptakan kehamilan yang sehat dan aman. Penelitian ini bertujuan untuk mengetahui hubungan dukungan keluarga dengan pemanfaatan buku KIA. Penelitian ini menggunakan pendekatan kuantitatif non eksperimental dengan desain cross sectional. Sampel terdiri dari 74 ibu hamil yang melakukan ANC di Puskesmas Kasihan 1 Bantul Yogyakarta, dipilih melalui teknik random sampling. Data dikumpulkan menggunakan kuesioner dukungan keluarga dan pemanfaatan buku KIA. Hasil penelitian menunjukkan bahwa mayoritas responden berusia 20–35 tahun (90,5%), berpendidikan terakhir SMA (52,7%), tidak bekerja (70,3%), dan berstatus multigravida (70,3%), dan sebanyak 38 (51,4%) responden berada pada trimester ketiga kehamilan, dan (50,0%), responden memiliki tingkat dukungan keluarga yang rendah namun tetap memanfaatkan buku KIA, yaitu sebanyak 41(55,4%). Berdasarkan Uji chi-square menunjukkan adanya hubungan yang signifikan antara dukungan keluarga dan pemanfaatan buku KIA.Kata Kunci: Dukungan Keluarga, Buku KIA